Ethnobotanical Study of Medicinal Plants in Zarivar Region (Marivan), Iran - MA Tabad; N Jalilian (Institue of Medicinal Plants, ACECR, 2015)
Background: Zarivar region, with about 5,000 km2 area, is located in the west of Iran, neighboaring the Marivan city. This region has a rich floral diversity due to some ecological factors such as: the average annual precipitation (about 997 mm/year), influence of the mediteranean water masses and situation within zagros mountain. Objective: The aim of this study was to identify medicinal plants flora of the Zarivar region and introducing some information of local herbal plants. Methods: Definition of the area was done based on 1:65000 topographic maps, then medicinal plant specimens were collected during years 2012-2013. Local knowledgeable people were questioned about usages of medicinal plants and data were recorded. Collected plants were deposited and identified in Herbarium of Agriculture and Natural resources research center of Kermanshah. Results: Overally 56 medicinal plant species belonging to 48 genera and 24 families were determined. Lamiaceae with 12 species and Asteraceae with 11 species had the highest species richness respectively. The most folk medicine were used for the treatment of gastrointestinal disorders. Conclusion: Results showed that numerous and valuable medicinal plants were found in Zarivar region. Traditional usage of medicinal plants is more accepted among people of the area. So, further studies may be more effective from pharmacological view of point.